Impact of family environment on mental disorders and quality of life in children with type 1 diabetes mellitus: a cross-sectional study and intervention policy analysis - Liu, Jing; Li, Jinhong; Li, Lichang; Zeng, Kun (Frontiers in Pediatrics, 2025)
BackgroundType 1 diabetes mellitus (T1DM) is common in adolescents and negatively affects their quality of life and mental health. This study examines the impact of family environment on mental disorders and quality of life in adolescents with T1DM and analyzes related intervention policies.MethodsA retrospective analysis was conducted on 75 adolescents with T1DM admitted between October 2020 and December 2023, with 75 healthy adolescents as a control group. Assessments included SCARED, DSRSC, FES, SCL-90, and PedsQL 4.0. Correlation analysis explored the relationships between family environment, anxiety, depression, quality of life and glycosylated haemoglobin (HbA1C).ResultsSignificant differences (P < 0.05) were found between the T1DM and control groups in family conflict, independence, harmony, and emotional expression. The T1DM group had higher anxiety, depression, and poorer quality of life. Family cohesion was negatively correlated with mental state, anxiety, depression, and HbA1C, while emotional expression was positively correlated with role functioning.ConclusionThe family environment significantly impacts the mental health and quality of life of adolescents with T1DM. Enhancing emotional expression and family cohesion can improve outcomes, highlighting the need for targeted interventions.